GE_GERICHTE C/1129/2015 vom 17. Oktober 2016 - GE Cour de justice (2016)
BAIL À LOYER; RÉSILIATION; USAGE PERSONNEL | CO.272.1; CO.272b.1; CO.257c; CO.267.1; CPC.243.2.c; CO.271a.1.e.1; CO.271a.3.a; CO.266a.2